Phytochemical Screening of propolis samples from Northeast Brazil by HPLC: Green, black and red varieties (Research, Society and Development, 2020)
Propolis is a natural resin made by bees of the genus Apis sp., And because of its antioxidant and antimicrobial activity, it has been used frequently in alternative medicine in several places of the world. These biological characteristics are related to their chemical composition, precisely to the phenolic compounds that vary in relation to their structure and concentration depending on the region of production, availability of plant sources for resin collection and time of year. Several experiments have been conducted in order to define the compounds that characterize these activities. The aim of this study was to elaborate and identify the chemical composition of the hydroalcoholic extracts of red, green and black propolis by High Performance Liquid Chromatography. The profiles presented by High Efficiency Liquid Chromatography (HPLC) of the extracts of the green, red and black propolis samples were very similar, but there was a great variation in terms of quantitative profile, besides playing an essential role in the antioxidant activity. Through the chromatograms, it is verified that as a function of the concentration of propolis, different phenolic compounds are extracted from the propolis, resulting in extracts with different biological properties. These data contribute to the knowledge of the biological activity of the hydroalcoholic extract of green propolis, favoring the search for new therapeutic agents.